Resolusi Konflik Ideologis dan Upaya Mendorong Konversi Keberagamaan Islam Fundamental Melalui Kepemimpinan dan Manajemen Pendidikan - Syaikhu Rozi (Proceedings of Annual Conference for Muslim Scholars, 2018)
Differences of interpretation of the Qur'an and As-Sunnah and differences in attitude in the face of modernization with all the causes and impacts make Muslims have different religious styles, one of which is fundamentalist. The fundamentalist commitment of Islamists in maintaining identity and developing fundamentalist ideology in moderate Islamic educational institutions can create ideological conflict in educational institutions. Therefore, it is necessary to solve it by encouraging the conversion of Islamic religious fundamentals by applying a leadership model that gives high attention to the completion of tasks and people (subordinates) and applying the approach of group/democratic management.